The relationship between the oblique sagittal temporomandibular joint disc position and the volume surface area of the condyle in young TMD adults - Gao, Yudong; Luo, Dan; Yuan, Mujie; Yang, Yanhao; Xu, Zexian; Yang, Jianjun (Frontiers in Bioengineering and Biotechnology, 2023)
The present study aims to compare the volume surface area of the condyle, the horizontal condylar axial angle and the disc-condyle angle between temporomandibular disorder (TMD) and asymptomatic volunteers, explore and analyze the relationship between the temporomandibular joint (TMJ) disc position in oblique sagittal plane and the volume surface area of the condyle in young adults with TMD symptoms. 84 young adult volunteers were received TMJ examination by Magnetic Resonance Imaging (MRI) and Cone Beam Computed Tomography (CBCT). TMD and asymptomatic volunteers were 42 each. MRI was used to assess the position of TMJ disc in the oblique sagittal plane with the condyle apex method. CBCT data were used for three-dimensional (3D) reconstruction of condyle and the measurements of the horizontal condylar axial angle and the volume surface area of the condyle. The condylar volume surface area of the TMD group was smaller than that of the asymptomatic group (p < 0.05), the disc condyle angle was larger than that of the asymptomatic group (p < 0.05), and no significant difference was found in the horizontal condylar axial angle (p > 0.05). In terms of correlation, the volume surface area of the condyle were negatively correlated with the position of the articular disc in TMD patients (p < 0.05). This significant negative correlation suggests that the possibility of disc displacement can be considered when poor condylar morphology is found.